A Theory of Debt Market Illiquidity and Leverage Cyclicality - Hennessy, Christopher A.; Zechner, Josef (Review of Financial Studies, 2011)
We analyze determinants of secondary debt market liquidity, identifying conditions under which a large investor can profitably buy stakes from small bondholders and offer unilateral debt relief to a distressed firm. We show that endogenous trading by small bondholders may result in multiple equilibria. Some equilibria entail vanishing liquidity and sharp increases in yields absent changing fundamentals. In turn, anticipation of illiquid equilibria induces firms to eschew public debt financing, since such equilibria create higher bankruptcy costs and debt illiquidity discounts. The model thus offers a rational micro-foundation for stylized facts commonly attributed to investor sentiment and CFO market timing. Finally, we show that the vulnerability of debt markets to multiple equilibria is highest during downturns, when small bondholders face severe adverse selection. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.